Clinical and personal utility of genomic high-throughput technologies: perspectives of medical professionals and affected persons. Issue 2 (3rd April 2018) - Urban, Alexander; Schweda, Mark
Abstract : In the evaluation of genomic high-throughput technologies, the idea of "utility" plays an important role. The "clinical utility" of genomic data refers to the improvement of healthcare outcomes, its "personal utility" to benefits that go beyond healthcare purposes. Both concepts are contested. Moreover, there are only few empirical insights regarding their interpretation by those professionally involved or personally affected. Our paper presents results from qualitative research (20 semi-structured interviews) regarding professionals' and personally affected people's views on the utility of genomic information. We find that the discussion of clinical utility is the domain of professionals who primarily consider aspects of test validity and clinical outcomes. By contrast, personal utility plays a prominent role in affected persons' discussions. Four different aspects are addressed: (a) life and family planning, (b) relief and justification, (c) self-knowledge and self-determination, and (d) entertainment. These differences have important implications for informed consent and counseling in the context of genomic high-throughput technologies.